The scarecrow and his servant [compact disc, unabridged] - Pullman, Philip, 1946- (Random House/Listening Library, 2005)
A scarecrow and his boy servant, Jack, set off on a dangerous adventure as they try to outwit the crooked Buffaloni family and stake their claim to valuable Spring Valley.